Longitudinal Changes in Smoking Behaviors and Cancer-Related Mortality Risk in Middle-Aged Korean Women - Tran, Thi Xuan Mai; Kim, Soyeoun; Kim, Seonju; Park, Boyoung (Cancer research and treatment, 2024)
Purpose This study investigated association between smoking habit change and cancer-related mortality risk in Korean women.Materials and Methods Study population were women aged ≥ 40 years who underwent two biennial cancer screenings during 2009-2012 and were followed up until 2020. Participants were grouped into sustained nonsmokers, sustained quitters, new quitters, relapsers/smoking initiators, and sustained smokers. Outcomes included all-cause and cancer-related deaths. Cox regression and competing risk analysis was used to assess association between smoking habit change and mortality risk.Results Of 2,892,590 women, 54,443 death cases were recorded (median follow-up of 9.0 years). Compared with sustained nonsmokers, mortality risk from all causes and cancer-related causes increased in all other smoking groups. Cancer-related risk increased 1.22-fold among sustained quitters (95% confidence interval [CI], 1.10 to 1.36), 1.56-fold (95% CI, 1.40 to 1.75) in new quitters, 1.40-fold (95% CI, 1.21 to 1.62) in relapsers/smoking initiators, and 1.61-fold (95% CI, 1.46 to 1.78) in sustained smokers compared with sustained nonsmokers. Women who were sustained smokers with higher smoking intensity had a higher mortality risk in terms of hazard ratios compared to nonsmokers (< 5 pack-years 2.12-fold, 5-10 pack-years 2.15-fold, and > 10 pack-years 2.27-fold).Conclusion Quitting smoking earlier is critical for preventing death from all causes and cancer among female smokers.